Perbedaan Metode Mind Mapping dan Concept Mapping Terhadap Hasil Belajar Kognitif Mata Pelajaran IPA Kelas V SD - Beta Feronika Agustin; Septi Budi Sartika (JURNAL ARMADA PENDIDIKAN, 2026)
This study aims to describe the differences between the Mind Mapping and Concept Mapping Methods on cognitive learning outcomes in science class V at SDN Sugihwaras. This study used a Quasi-Experimental Design quantitative method using a Mathing Pretest – Posttest Control Group Design. The population in this study were students in grades V/C and V/D at SDN Sugihwaras, each class consisting of 30 students. The samples taken were students in class V/C and V/D at SDN Sugihwaras, each class consisting of 30 students. The data collection technique in this study is by using multiple choice tests. The instrument used in this study was multiple choice questions totaling 25 items which had been validated by two experts in their field. The data analysis technique used in this study is the Normality test, Homogeneity test and Hypothesis test. After testing the hypothesis using the Anova test, the result is that the sig. 0.750 > 0.05 for the Mind Mapping class and sig. 0,368 < 0.05. So it can be concluded that there is a difference between the Mind Mapping and Concept Mapping classes.